(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
The female inflorescence of Scindapsus officinalis (Roxb.) Schott commonly known as Gajapippali is an important Ayurveda drug of Araceae family. A market survey revealed that the inflorescence of Borassus flabellifer L., a completely unrelated plant species, is traded as Gajapippali owing to its morphological similarities. The botanical identity of medicinal plants is of utmost importance for research as a raw drug’s medicinal efficacy and therapeutic properties vary with botanical source. This study aims to validate the key identifying features of the unofficial source of Gajapippali with the help of pharmacognostical techniques, including DNA Barcoding. Pharmacognostical fingerprinting of the male inflorescence of B. flabellifer was carried out by macro-microscopy, physicochemical analysis, HPTLC, and DNA-based molecular methods to identify the botanical precisely. Morphology was carried out using macroscopy, and the anatomical parameters were studied using microscopy. In addition, phytochemical studies were conducted with the help of HPTLC fingerprinting. The nucleotide sequencing using rbcL marker was carried out for species identification, and a barcode was generated. The morphology of the male inflorescence by macroscopy, tissue arrangements at the cellular level by microscopy of transverse section and powder, purity determination by physico-chemical methods and phytoconstituents fingerprinting using HPTLC showed key identifying features of the inflorescence. The conserved DNA sequence showed the homology of the species, which was submitted to NCBI and converted to a barcode for identification of the botanical. This study will be helpful in the identification and determination of B. flabellifer, the market source of Gajapippali, and help in the purity check and quality control of this herbal raw material used in place of the official source.